Digital Politics and Participation Politics in Society in the Era of Industrial Revolution - Salim, Kamaruddin (Indonesian Journal of Digital Society is a scientific journal, 2020)
Digital politics and public political participation in the 4.0 revolution era provide interesting themes in political studies in Indonesia. In political contestation along with the holding of the General Elections of President and Vice President and the Election of Legislative Members simultaneously in 2019, with the increasing level of public political participation, at least one of the important elements that encourages increased public participation is the role of social media. Social media has become a space for effective political interaction for all sections of society to access information, especially in the era of the industrial revolution 4.0 where the internet media has become a space for political battles both political actors and supporters of Candidates for Presidential Candidates. Digital politics is developing into a new space in realizing dynamic democracy, so the political communication that is built through social media is starting to become a place for political actors to offer ideas and political programs to the public. So this development gives that the future of Indonesian democracy is becoming more modern. by conducting descriptive analytical research in order to understand the digital political process and political participation which are the most important learning media for society in politics.Keywords: Digital politics, political participation, direct elections, and democracy.